Effect of fluid intake volume on 2-h running performances in a 25°C environment - Daries, H. N.; Noakes, T. D.; Dennis, S. C. (Medicine & Science in Sports & Exercise, 2000)
Purpose: In this study, we examined the effects of greater than ad libitum rates of fluid intake on 2-h running performances.